2019
DOI: 10.1038/s41598-019-53713-1
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of AlN-based flexible piezoelectric pressure sensor integrated into an implantable artificial pancreas

Abstract: This study reports on the fabrication and characterization of an event detection subsystem composed of a flexible piezoelectric pressure sensor and the electronic interface to be integrated into an implantable artificial pancreas (IAP) for diabetic patients. The developed sensor is made of an AlN layer, sandwiched between two Ti electrodes, sputtered on Kapton substrate, with a preferential orientation along c-axis which guarantees the best piezoelectric response. The IAP is made of an intestinal wall-interfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 33 publications
0
16
0
1
Order By: Relevance
“…This leads to a rapid decrease in the piezo output which finally reaches to zero. When the force is released, the piezoelectric polarisation disappears, giving rise to a negative peak (electrons flows in backwards direction to achieve the new equilibrium) [47].…”
Section: A Aln Piezocapacitor Characterisationmentioning
confidence: 99%
See 1 more Smart Citation
“…This leads to a rapid decrease in the piezo output which finally reaches to zero. When the force is released, the piezoelectric polarisation disappears, giving rise to a negative peak (electrons flows in backwards direction to achieve the new equilibrium) [47].…”
Section: A Aln Piezocapacitor Characterisationmentioning
confidence: 99%
“…as it exhibits efficient piezoelectric and dielectric properties, high thermal stability, as well as low dielectric loss tangent and high signal to noise ratio [35][36][37]. Additionally, no poling or stretching is needed [38].…”
mentioning
confidence: 99%
“…[256][257][258][259][260] However, the fabrication of high-performance pressure sensors based on WBG semiconductor nanowires, especially for SiC, group III-nitrides, and diamond, are very rare. [261][262][263] For instance, Phan et al reported an effective approach to develop highly sensitive pressure sensors employing 3C-SiC nanowires fabricated at the center of a dogbone-like structure. [261] Figure 12a shows a photograph of SiC nanowire-based pressure sensors mounted on an acrylic holder.…”
Section: Pressure Sensorsmentioning
confidence: 99%
“…[ 40 ] PSs have been applied for monitoring physico‐chemical health parameters or as nanogenerators (PENGs) for harvesting human energy to supply portable/implantable biomedical devices. [ 41,42 ] In this work, a thin film of transparent lead‐free inorganic aluminum nitride (AlN) piezo‐ceramic [ 43,44 ] has been employed as piezoelectric material on flexible polyimide (PI), chosen for its high temperature, mechanical and chemical stability. [ 45,46 ] AlN exhibits advantageous properties: heat‐ and humidity‐resistance, [ 47 ] biocompatibility, [ 40,48 ] CMOS compatibility, good piezoelectric, and dielectric properties both on rigid and flexible substrates.…”
Section: Introductionmentioning
confidence: 99%